Flameless Oxidation of liquid fuel oil in a reverse-flow cooled combustion chamber. (August 2017) - Luhmann, H.; Maldonado, F. Carrasco; Spörl, R.; Scheffknecht, G.
Abstract: This paper presents the experimental results on flameless oxidation of light fuel oil in a reverse-flow cooled combustion chamber. NOX and CO emissions as well as temperatures in the combustion chamber are used to determine combustion performance of the cold air flameless oxidation (FLOX ® ) burner. Five different twin fluid atomizers with varying spray angles between 0° and 80° and different bore diameters have been used and the influence of atomizing air pressure between 4 and 6 bar on the combustion performance was investigated. In the tests air stoichiometry ratios ranged from 1.1 to 1.9 and thermal inputs were varied between 50 and 150 kW. Results show that good combustion performance in flameless mode was achieved. Low NOX emissions combined with low CO emissions which meet strictest CO (according to DIN EN 267 class 3 burners, 60 mg/kWhth ) and NOX regulations (according to 1. BImSchV, 110 mg/kWhth ) were obtained at an air ratio of 1.1.